Comparison of Wireless Data Communication System (WDCS) Antenna in Between MRT Kajang Line and MRT Putrajaya Line - Sarmilee, Muhammad Zamakhsyari (Progress in Engineering Application and Technology, 2022)
Establishing solid communications between a fast-moving train and the trackside is one of the most difficult challenges in modern rolling stock systems. Wireless technologies are widely utilised in train-to-ground applications for Bi-directional and Omni-directional communications, and selecting the right wireless technology for each rail system is crucial.Basically, a wireless network consists of data, voice, and video information packets being transmitted over low-frequency radio waves instead of electrically over copper cable or via light over fiber lines. Having the correct antennas is one of the most important aspects of running a successful wireless network. Antennas exist in a variety of shapes and sizes, each with its own function. The correct antenna must be chosen in a network to provide optimal network performance. Furthermore, choosing the proper antenna can assist reduce the quantity of antenna use on the site while also lowering the cost of expenses.The focus of this research is to proof that which design of antennas used in wireless data communication systems give more benefits in railway application. This research includes comparing background information on wireless data communication systems (WDCS) between MRT Kajang Line and Putrajaya Line. Aside from that, antenna principles such as antenna type, position, and frequency usage will be examined.